Characterisation of pharmacogenomic variation in the Shetland and Orkney Isles in Scotland - Twesigomwe, David; Aitman, Timothy J.; Wilson, James F. (Scientific reports, 2025)
Genetic variation is partly responsible for variability in drug response across populations. However, the full catalogue of pharmacogenetic variants and their distribution are yet to be established, thus posing challenges in implementing individualised medicine in understudied populations. This study aimed to characterise variation in key drug response genes across founder populations from the Northern Isles of Scotland. We analysed whole genome sequence datasets from 498 Shetlanders and 1372 Orcadians, the majority of whom are research participants in the Viking Genes programme, and compared the genetic variation in 41 selected pharmacogenes with observed distributions in other European datasets. From this gene-set, we present frequencies of known and potentially novel star alleles (haplotypes and structural variants) for 18 core pharmacogenes analysed using StellarPGx, and variant distributions in 23 other selected pharmacogenes with existing clinical annotations in ClinPGx ( https://www.clinpgx.org ). Despite important differences in the frequencies of rare and/or novel potentially high-impact variants, the distributions of the well-studied common actionable pharmacogene star alleles do not vary dramatically across Shetland, Orkney, and the European populations represented in the 1000 Genomes Project or allele frequency meta-analyses in ClinPGx. Importantly, for gene-drug pairs with Clinical Pharmacogenetics Implementation Consortium Guidelines, we estimated (based on diplotypes alone) that the proportion of participants in the combined dataset that may benefit from a change in dose/drug ranged from 0 to 50.5%, depending on the gene-drug pair. Overall, understanding the landscape of pharmacogenomic variation in Shetland and Orkney is an important step towards implementation of precision medicine across rural Scotland.